Management of damping-off of chillies with plant products - R. PADMAVATHI, V. KURUCHEVE and (Indian Phytopathology, 2002)
Bulb extracts of garlic, leaf extracts of Lawsonia inermis, Eucalyptus globulus and Azadirachta indica, oil cake extract of sesame, and thiram, were tested in pot culture for the control of damping off of Capsicum annuum caused by Pythium aphanidermatum. Thiram gave the best control followed by garlic bulb extracts and leaf extracts of L. inermis.